Water vapour line parameters from microwave to medium infrared (an atlas of H₂ ¹⁶O, H₂ ¹⁷O, and H₂ ¹⁸O line positions and intensities between 0 and 4350 cm⁻¹) - Flaud, J.-M (Tables internationales de constantes selectionnees ;, 1981)
Water Vapour Line Parameters from Microwave to Medium Infrared (An Atlas of H2 16O, H2 17O, and H2 18O Line Positions and Intensities Between 0 and 4350cm-1) is the culmination of long-range effort and represents a large amount of analysis and calculations relating to the properties of water molecules. The text is divided into major parts. The first half discusses the theories, and the second half presents the atlas. The atlas provides the position, the intensity, the lower energy level, the rotational and vibrational quantum numbers of the upper and lower levels, and the isotropic species. Th.